2019
DOI: 10.1002/jlb.3mir1118-417r
|View full text |Cite
|
Sign up to set email alerts
|

Cells under stress: The mechanical environment shapes inflammasome responses to danger signals

Abstract: Many intracellular signals, such as host danger-associated molecules and bacterial toxins during infection, elicit inflammasome activation. However, the mechanical environment in tissues may also influence the sensitivity of various inflammasomes to activation. The cellular mechanical environment is determined by the extracellular tissue stiffness, or its inverse, tissue compliance. Tissue stiffness is sensed by the intracellular cytoskeleton through a process termed mechanotransduction. Thus, extracellular co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 71 publications
(95 reference statements)
0
22
0
Order By: Relevance
“…Based on the current understanding of the molecular pathogenesis of ASD, a genetic background would confer the activation of innate immunity in response to environmental factors [12]. Damage-associated molecular patterns can activate innate immunity [17], and it was hypothesized that changes in several DAMPs are associated with ASD and mediate autoin ammatory cascade by activation of in ammasome [13]. CIRP is induced by cellular stresses and functions as a DAMP molecule that promote in ammatory responses [4].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the current understanding of the molecular pathogenesis of ASD, a genetic background would confer the activation of innate immunity in response to environmental factors [12]. Damage-associated molecular patterns can activate innate immunity [17], and it was hypothesized that changes in several DAMPs are associated with ASD and mediate autoin ammatory cascade by activation of in ammasome [13]. CIRP is induced by cellular stresses and functions as a DAMP molecule that promote in ammatory responses [4].…”
Section: Discussionmentioning
confidence: 99%
“…(B) The immune system is essential for allostasis (2,3,4), development and reproduction. Sterile tissue damage such as psychological (36) or physical trauma (37), mechanical stress (38) or ischemia/reperfusion injury (e.g. myocardial infarct) induces an inflammatory reaction promoting wound healing and/or regenerative mechanisms.…”
Section: Figurementioning
confidence: 99%
“…At the cardiovascular level, immune cells (activated either by a psychological or physical stressor) interact with endothelial cells, cardiac stromal cells and cardiomyocytes, which adapt their metabolism to support the ongoing inflammatory process (upper part right panel). In the heart (lower side of the right panel), the stress signal can mediate the activation of the intracellular transduction pathways linked to mTOR ( 39 ) and NfKB ( 40 ) genes through the mediators of the PNEI system (i.e hormones, neurotransmitters and cytokines). This will influence the cellular energy metabolism with high oxidative stress and damage from free radicals ( 41 ), misfolding of proteins ( 42 ) or their abnormal synthesis (alternative splicing) ( 43 ).…”
Section: Cardiac Myocytes Fibroblasts Endothelial Cells Pericytes mentioning
confidence: 99%
“…Release of PAMPs and DAMPs caused by profibrotic injury or infection leads to inflammasome activation, and there are several different kinds of inflammasome scaffolds that can form. Interestingly, it has been suggested that as fibrosis progresses and the lung stiffens, the increased mechanosensing by cells in the lung may lead to ongoing inflammasome activation as a way to perpetuate lung fibrosis . For example, vimentin has recently been identified as important for inflammasome activation and mice deficient in vimentin are protected from bleomycin‐induced fibrosis and do not stimulate IL‐1β production in response to bleomycin .…”
Section: The Inflammasome In Lung Fibrosismentioning
confidence: 99%
“…Interestingly, it has been suggested that as fibrosis progresses and the lung stiffens, the increased mechanosensing by cells in the lung may lead to ongoing inflammasome activation as a way to perpetuate lung fibrosis. 20 For example, vimentin has recently been identified as important for inflammasome activation and mice deficient in vimentin are protected from bleomycin-induced fibrosis and do not stimulate IL-1b production in response to bleomycin. 21 This idea of mechanical feed forward innate immune activation is an interesting hypothesis about how fibrosis becomes progressive.…”
Section: The Inflammasome In Lung Fibrosismentioning
confidence: 99%